(untitled) (Research, Society and Development, 2022)
Introduction: It is estimated that 20-30% of the world population is accepted for respiratory allergies. The diagnosis is made based on the clinical history, the physical examination and a survey of the total IgE. Since the 1990s, increased body mass index (BMI) has been associated with a higher prevalence of asthma in adults. Objective: To correlate BMI with total IgE levels of patients treated in a structured asthma program in São Luís-MA. Methods: 158 patients enrolled in the Non-Asthma Patient Support Program of the São Luís-MA. The bound enzyme-linked immunosorbent assay was used to quantify total IgE levels. Patients were stratified according to BMI. Approved with the opinion of no. 406/06. Results: A total of 158 patients with a diagnosis of asthma were studied, with 71 patients with both rhinitis and sinusitis. There was a predominance of females (120/158, 75.9%) and urban residents (112/158, 70.9%). The mean age was 46.13 (± 13.90) years. Sixty (38.0%) and overweight and 24 (15.2%) were obese. A mean total IgE between the cases was 2.49 (± 1.09). Total IgE levels were higher in the male gender (p = 0.01). Conclusions: The majority of overweight and obese patients presented elevation in total IgE levels, with no significant statistical significance (p = 0.72).